Biology Teacher's Perception in Accommodating 21st Century Learning Demands - Suganda, Handi; Riandi, Riandi; Purwianiangsih, Widi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The teacher is the main factor that contributes to 21st century learning which has four aspects, namely 1) creativity, 2) critical thinking, 3) communication, 4) collaboration. Characteristics of 21st century learning include the integration of technology in learning which is a component of TPACK (Technological Pedagogical and Content Knowledge). This study aims to describe the perceptions of biology teachers in accommodating the demands of 21st century learning. This research is a descriptive study with survey methods. The study population was biology teachers who were included in the Biology Subject Group Consultative Group (MGMP) in Bandung Regency. The research sample is four biology teachers who teach in class XI of High School (SMA) in two schools in the district of Bandung. Teacher perceptions data obtained from the teacher's answer to the 21st century skills, learning questionnaire and a teacher's consideration questionnaire in integrating technology in 21st century learning. The results showed the teacher had understood that 21st century learning must include all four aspects of 21st century learning, but in the aspects of creativity and critical thinking the teacher was still unsure of the learning evaluation process. Teachers have also understood the importance of technology integration in 21st century learning, but in the aspects of Technological Content Knowledge (TCK) teachers are still not optimal